Incidence of metachronous gastric cancer after endoscopic submucosal dissection associated with eradication status of Helicobacter pylori. Issue 1 (January 2021) - Ikeda, Ryosuke; Hirasawa, Kingo; Sato, Chiko; Sawada, Atsushi; Nishio, Masafumi; Fukuchi, Takehide; Kobayashi, Ryosuke; Makazu, Makomo; Kaneko, Hiroaki; Maeda, Shin
Abstract : Objective: This study compared the clinicopathological features and treatment outcomes of patients with primary early gastric cancers (EGCs) who had undergone Helicobacter pylori eradication and endoscopic submucosal dissection (ESD) with those of patients who were H. pylori -positive and had undergone ESD. Additionally, we investigated the incidence of metachronous cancer in these patients. Methods: We retrospectively analyzed 1849 EGCs in 1407 patients who underwent ESD whom 201 primary EGCs were detected after H. pylori eradication (eradication group) and 1648 primary EGCs were detected in patients infected with H. pylori (infection group). We evaluated the clinicopathological features and treatment outcomes of the first ESD. We next divided 938 patients whose follow-up periods were >1 year into three groups, an eradication group ( n  = 61), an infection group ( n  = 562), and an eradication after ESD group ( n  = 315). The groups' cumulative metachronous occurrence rates were determined. Results: The eradication group's median tumor size was significantly smaller, and the tumors were significantly more likely to be flat/depressed than those in the infection group. The groups did not differ regarding the treatment outcomes. The cumulative incidence of metachronous cancer was significantly higher in the eradication group than in the eradication after ESD group ( P  = 0.0454) and in the infection group than in the eradication after ESD group ( P  = 0.0233). Conclusion: The treatment outcomes for EGC in the eradication group were favorable. The higher incidence of metachronous cancer in the eradication group suggests that careful endoscopic follow-up examinations are required. Abstract : Supplemental Digital Content is available in the text.